Predictors of Job Crafting Behaviors: A Mediation Analysis - Silva de Carvalho Chinelato, Renata (2021)
The study explored the relationship between psychological safety and job crafting behaviors, as well as the mediating role of the satisfaction of psychological needs in this relationship. The sample was composed of 1,171 Brazilian workers, who answered the Psychological Safety Scale, the Basic Needs Satisfaction General Scale and the Job Crafting Scale. The structural equations modeling showed that the perception of psychological safety contributed to the satisfaction of psychological needs which, in turn, affected the job crafting behaviors. It was concluded that the job crafting behaviors suffer from the influence of contextual work resources and motivational aspects, which contributes to the understanding of the effects of the new demands of work on organizational behavior.